Circadian rhythms in Neurospora crassa: a mutation affecting temperature compensation. - Mattern, D L (1982)
The circadian rhythm of conidiation (spore formation) in Neurospora crassa is known to be temperature compensated, that is, the period is only slightly affected by the incubation temperature. Thus, the Q10 (the relative rate enhancement corresponding to a 10 degrees C rise in temperature) of the rhythm of the bd csp strain from 14 to 30 degrees C was 1.1, whereas the Q10 of the uncompensated growth rate in the same interval was 2.4. A mutation at the cel locus resulted in loss of the temperature-compensation property in cultures grown below 22 degrees C. The Q10 of the rhythm below 22 degrees C was 2.2, and periods of about 40 hr were observed. In contrast, the Q10 of the rhythm above 22 degrees C was 1.1, with circadian periods of 18-21 hr. Thus, cel displayed a threshold temperature or "break point" for the temperature compensation of its rhythm. Supplementation of cel strains, which require fatty acids, with unsaturated or short-chain fatty acids raised the threshold temperature to 26 degrees C, whereas supplementation with long-chain saturated fatty acids lowered it to 18 degrees C. These data suggest a role for fatty acids, as liquid components or as cellular metabolites, in the mechanism of temperature compensation.